Transformation Of Land Ownership And Transfer Of Rights For Legal Entities And Foreign Individuals After The Effectiveness Of Regulation Of The Minister Of Atr/Head Of Bpn RI Number 5 Of 2025 - Sihutami, Veronica Kinanthi; Nordyaningrum, Najwa Yorry (Journal of Law, Politic and Humanities, 2025)
The Ministerial Regulation of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (Permen ATR/Kepala BPN) Number 5 of 2025 introduces a new legal framework governing land ownership and transfer rights in Indonesia, specifically for legal entities and foreign nationals. The regulation marks a significant milestone in accommodating global economic developments and foreign investments while safeguarding national land sovereignty. This study aims to analyze the substantive changes introduced by the regulation, assess its legal implications for legal entities and foreign nationals, and evaluate how well it balances economic development interests with the protection of agrarian rights for Indonesian citizens. The research adopts a normative juridical approach with comparative analysis of previous regulations and document studies. The findings indicate that Permen ATR/Kepala BPN Number 5 of 2025 provides improvements to the mechanisms of land ownership limitations while offering more adaptive space for foreign investment interests. Nevertheless, its implementation may pose legal challenges, especially in the areas of monitoring and resolution of agrarian disputes. Therefore, this regulation requires strengthened oversight mechanisms and enhanced protection of land rights to prevent imbalances and legal conflicts.